Gaya Bahasa Kiasan dan Rima dalam Nyanyian Rakyat Suku Rejang di Desa Batu Roto - Silviyana, Silviyana; Irwan Satria; Dina Putri Juni Astuti (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study aims to analyze the figurative language style and rhyme found in the folk songs of the Rejang Tribe in Batu Roto Village. The method used in this study is descriptive qualitative with a stylistic approach. Research data were collected through direct observation of folk songs performed by the local community, as well as interviews with several informants who have knowledge of the oral tradition. The results of the study indicate that figurative language styles, such as metaphors, personifications, and comparisons, are widely used in Rejang folk songs to describe daily life, beliefs, and human relationships with nature. In addition, the rhyme used in these folk songs provides a rhythmic impression and facilitates people's memory in transmitting stories or messages. Rhyme also functions as a tool to strengthen the emotional nuances to be conveyed through the song. In the cultural context of the Rejang Tribe, figurative language styles and rhymes not only function as tools of artistic expression but also have deep educational and symbolic values ​​for the local community. In conclusion, this study can contribute to the study of Indonesian oral literature, particularly regarding the role of figurative language styles in folk songs as one of the cultural heritages that must be preserved. Keywords: Figurative Language Styles, Folk Songs, Rejang Tribe, Rhymes.